Resin flow monitoring inside composite laminate during resin film infusion process. Issue 4 (17th October 2013) - Zhou, Z.J.; Li, M.; Gu, Y.Z.; Ma, X.Q.; Li, Y.X.; Jia, L.J.; Zhang, Z.G.
<x xml:space="preserve">Abstract</x> In this article, a novel method of measuring resin flow front under vacuum condition is presented. The in situ monitoring system with metal hollow probe based on gas flow balance can be used in resin film infusion (RFI) process, where resin film is used and transverse flow is dominated along thickness direction of fiber preform. The diameter of the probe was chosen to increase the measuring accuracy, and the reliability of the method was evaluated by comparison of visualization experiment. Experimental results demonstrate that the method is suitable for monitoring resin flow in RFI process with and without autoclave, and can obtain the information about resin filling time, nonuniform flow front, and the permeability of fiber preform. Furthermore, by means of the established monitoring system, the influences of pressure and lay‐up sequence of carbon fiber fabric on epoxy resin flow during RFI process were investigated. In addition, resin flow pattern with changing viscosity of epoxy resin was studied. POLYM. COMPOS., 35:681–690, 2014. © 2013 Society of Plastics Engineers